ACUTE ISCHEMIC STROKE RISK FACTORS STRATIFICATION MODEL IN ISOLATED VERTIGO PATIENTS: TWO-YEARS COHORT RETROSPECTIVE STUDY - Faizal Muhammad; Rivan Danuaji (Magna Neurologica, 2026)
Background: Vertigo is a common complaint in medical settings, with the most important differential diagnosis to exclude being vertebrobasilar ischemic stroke. However, there have been no cohort studies evaluating the risk of stroke following hospitalization for acute vertigo without other neurological symptoms (isolated vertigo). Objective: To assess the long-term risk of stroke in patients with a history of hospitalization due to isolated vertigo. Methods: This retrospective cohort study was conducted at Dr. Moewardi Hospital in Surakarta, utilizing secondary data from electronic medical records for the years 2024–2025. A total of 268 patients hospitalized for vertigo and 223 control patients (elective gastrointestinal endoscopy patients) were selected based on similar age distribution. Stroke incidence data were analyzed using Kaplan-Meier methods and Cox regression, with adjustments for demographic variables and vascular risk factors. Results: Over a 2-year period, stroke occurred in 16 vertigo patients (5.8%) and 2 control patients (1.1%). After adjustment, vertigo patients had a 3.25-fold higher risk of stroke compared to the control group (HR: 3.25; 95% CI: 2.18–4.15; p = 0.002). Stroke risk significantly increased in patients with ≥3 vascular risk factors (HR: 5.01). Approximately 68% of strokes occurred within the first year. Conclusion: Isolated vertigo significantly increases the risk of ischemic stroke, particularly in patients with risk factors during the first year following the initial symptoms of isolated vertigo.